The Development of Jazz music in Thai Education Context - Kuabutr, Kamontam (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
This research study, the development of Jazz music in the Thai educational context, was the part of the research “Jazz Music in Thailand: Historical Context and Development”. The study was a qualitative research, and the data was collected in historical musicology. The aim of this study was to study history and development of Jazz music in the educational context in Thailand. The results of the research were found as follows. The research results were divided into 3 aspects, that is, 1) as for history and development of Jazz education in Thailand, it was initially started by senior musicians who had had Jazz experiences and taught other musicians. Additionally some musicians themselves could study by transcribing from records. It had lasted a number of years until a curriculum of music was initially applied to educational system in a university. In 1994, it came to the systematic education of Jazz music; that is, a college of music was established at Mahidol University, originating a course of teaching Jazz music. It could be said that this was the first course of Jazz music in Thailand. After a while, the courses concerning Jazz music were launched at Silpakorn University, Rangsit University, Burapha University, and Songkhla Rajabhat University, respectively. 2) In terms of educational activities that support Jazz education, a Jazz seminar and concert was first held by Mahidol University. Also, a Jazz competition was held by Silpakorn University. 3) For Jazz music courses in Thailand, they were developed by 5 educational institutions, namely, Mahidol University, Silpakorn University, Rangsit University, Burapha University, and Songkhla Rajabhat University. The subject matter of Jazz theories and music skills in different courses in different universities was similar, for instance, 7 - 8 subjects of Jazz skills, 4 subjects of ensemble, and so on. Among those universities, purposes and goals of teaching Jazz music were different. For example, research-related courses have been concentrated on in music curriculum at Silpakorn University, Burapha University, and Songkhla Rajabhat University. Whereas, Songkhla Rajabhat University was the only one focusing on music internship.